2018
DOI: 10.2147/ijwh.s168569
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, characteristics, maternal complications, and perinatal outcomes associated with preeclampsia with severe features and HELLP syndrome

Abstract: ObjectiveTo determine the incidence of preeclampsia with severe features among pregnant women and evaluate the characteristics, maternal complications, and perinatal outcomes between nonsevere preeclampsia versus preeclampsia with severe features and hemolysis, elevated liver enzyme levels, and low platelet levels (HELLP) syndrome.Materials and methodsA retrospective descriptive study was conducted at Khon Kaen University’s Srinagarind Hospital, a tertiary care facility in northeast Thailand. The pregnant wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 18 publications
6
50
0
9
Order By: Relevance
“…6,[11][12][13][14] Early-onset PE has a lower incidence than late-onset PE, with a frequencies reported to be 0.5% and 1.4 to 1.7%, respectively. 5,6,14,15 Preeclampsia can also be classified as preterm or term, according to whether delivery is needed before or after 37 weeks of gestation. 1,6,16 An impaired placentation is thought to be the underlying cause of PE, with complete resolution of the clinical manifestations within 12 weeks postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…6,[11][12][13][14] Early-onset PE has a lower incidence than late-onset PE, with a frequencies reported to be 0.5% and 1.4 to 1.7%, respectively. 5,6,14,15 Preeclampsia can also be classified as preterm or term, according to whether delivery is needed before or after 37 weeks of gestation. 1,6,16 An impaired placentation is thought to be the underlying cause of PE, with complete resolution of the clinical manifestations within 12 weeks postpartum.…”
Section: Introductionmentioning
confidence: 99%
“…(Waterstone et al (7) published that incidence of HELLP syndrome was 0.5/1000 deliveries (95 % CI 0.3-0.8) in South East Thames region . Kongwattanakul et al (14) wrote incidence of HELLP syndrome was 1.4/1000 deliveries in Thailand during years 2012-2016.…”
Section: Discussionmentioning
confidence: 98%
“…These findings are in accordance with all of the studies compared with Yildrim et al 6 39 patients (70.9%) of HELLP needed transfusion of blood or blood products. 15 Tandon et al 2016 reported comparable low incidence of maternal mortality in preeclampsia group -0.9%, but the incidence of mortality in HELLP syndrome group was high (18.18%). 5…”
Section: Maternal Outcomementioning
confidence: 95%